Factors related to the postoperative recurrence of lumbar disc herniation treated by percutaneous transforaminal endoscopy: A meta-analysis - Li, Honglin; Deng, Wei; Wei, Faqiang; Zhang, Liangmin; Chen, Fan (Frontiers in Surgery, 2023)
Objective: To explore factors related to the postoperative recurrence of lumbar disc herniation treated by percutaneous transforaminal endoscopy. Methods: PubMed, EMBASE, Cochrane Library, CNKI, Wanfang database and VIP database were systematically searched from the time of each library’s construction to October 20, 2022. The studies that compared the influencing factors of recurrent lumbar disc herniation were included based on the PICO search structure. The Newcastle–Ottawa Scale was used to evaluate the quality of observational studies. The effects of the patient’s age, gender, BMI, smoking, drinking, hypertension, diabetes, course of the disease, Pfirrmann grade, and the surgical segment on recurrent lumbar disc herniation were systematically evaluated using Revman 5.3. The odds ratio (OR) and 95% confidence interval (CI) were calculated. Results: Thirteen studies involving 3,393 patients (323 patients with recurrent lumbar disc herniation) treated with percutaneous transforaminal endoscopy were included in this study. The results of the systematic evaluation showed that the effects of gender, smoking, drinking, hypertension, type of lumbar disc herniation and the surgical segment on recurrent lumbar disc herniation were not statistically significant. However, age ≥60 years (OR = 2.23; 95% CI: 1.13, 4.41), BMI ≥25 (OR = 2.89; 95% CI: 1.23, 6.80), diabetes (OR = 1.73; 95% CI: 1.18, 2.55), course of disease ≥4 years (OR = 2.93; 95% CI: 1.58, 5.43), Pfirrmann grades 3–4 (OR = 3.10; 95% CI: 2.18, 4.40), incomplete removal of nucleus pulposus (OR = 3.26; 95% CI: 1.69, 6.27) and intraoperative fibre breakage (OR = 3.18; 95% CI: 1.56, 6.50) increased the risk of recurrence after treatment. Conclusion: The recurrence of lumbar disc herniation after percutaneous transforaminal endoscopic treatment is related to demographic characteristics, disease history and surgical conditions. In the future, more high-quality studies are needed to explore the influencing factors of recurrent lumbar disc herniation.